Response of Cayenne Pepper and Red Pepper Plants to The Concentration of Orrin Liquid Fertilizer on Entisol Soil - Fikranti, Annisa Anjung; Mulyati, Mulyati; Silawibawa, I Putu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study aims to determine the effect of orrin liquid fertilizer on the growth and yield of cayenne pepper and red peppers on Entisol. The research method used is an experimental method, carried out on farmer-owned land in Kediri village, Kediri District, West Lombok Regency from June to October 2023. The study consisted of two experimental units consisting of one unit for cayenne pepper and another unit for red chili, The experimental design used was a randomized group design, with the treatment of orrin liquid fertilizer concentration (0, 10, 20) ml / L Each treatment was repeated three times and the data observed were analyzed using analysis of variance, while the different treatment was further tested using BNJ 5%. The outcomes showed that the treatment of orrin fluid manure application didn't influence the development of cayenne pepper and red bean stew plants which include: plant level, number of leaves and number of stem branches), yet impacted the yield parts which include: organic product weight and number of natural products. While the timeframe of realistic usability of cayenne pepper can arrive at 35 days and red pepper 45 days without decay.